Ocupações urbanas e a (re) produção das moradias populares em Manaus: estudos no bairro do Coroado e loteamento Rio Piorini - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
The house presents itself as a necessary item reproduction of life. The dwell equates the need to eat and wear and is intrinsically related to the reproduction of capitalism, in turn dependent on labor. The dialectic between the need to living and reproduction of capitalism produces one of missing and/or insecurity in the home, as the urban land is occupied and fractionated as the financial conditions of the population that consumes the space through their ability to pay, and the lack of financial conditions, to impose the fadados periferização of space. As this item essential to reproduction of live, housing and goods particular, to live as individuals not only need a ceiling, if other elements are needed for the continuity the reproduction of life. The housing can be characterized on the one hand, with respect to its place in the whole economic system and the other as a product with specific characteristics: (CASTELLS, 1983: 225). At the heart of the issues related to housing, is facing its production through the illegal appropriation of urban land that can connote before anything else, as a demonstration of courage, strength and sometimes the will to live as human beings. In this context comes the city of Manaus which spatiality was shaped by means of housing popular occupied by illegal occupation of land. At the expense of many issues related to this subject, aimed to study the urban occupations in the city of Manaus to a point of departure the occupations of the river Piorini Coroado and blending. The first came in 1971 projected economic recovery in the city Manaus though the Free Zone in 2003 and the second time when the city was presented approximately 1.500.000 inhabitants. Based on this information preliminary, the study was directed to the understanding of why these occupations were originated and whether, even with time difference significant between the appearance of them, there are similarities in their production process. For this, the research is devoted to interview 50 (fifty) of booth the residents of the Rio Piorini and Coroado trough interviews open and closed forms. Similarly it was produced both the removal os information on these localities public bodies, as well as the contribution to the achievement bibliographic the final work that has the primary results, the finding of the even when dealing with different times, the production process the occupations under study was marked by conflicts involving the owners and occupants of the land that fought for the same purpose the acquisition of occupations of residents from both inside the state as in other localities of the Brazilian federation is not changed. Moreover, it appears that the crowned, now classified as neighborhood experienced the same conditions found at the beginning of the blending River Piorini: the lack of equipment for collective use being added little through the popular demand that we to palpitate the prognosis that the occupation Rio Piorini on whether building tends to acquire characteristics similar to the choir
Keywords: Assentamentos humanos; Ocupação territorial; OUTROS